Penerapan Tunneling Incentive Terhadap Transfer Pricing - Sarifatul Khotijah; Aminah Aminah; Farida Efrianti; Iskandar Ali Alam; Riswan Riswan (Universitas Bandar Lampung (UBL), 2022)
Globalization is increasingly growing rapidly and driving the world economy so it has quite a big impact on business actors. Not a few national companies in Indonesia are in the process of developing their business into a research company, this has the aim of being able to test how much influence taxes and tunneling incentives have on transfer pricing decisions at Indonesian Stock Exchange companies or often known as BEI companies in 2017- 2020. In the research process, the research used purposive sampling method and found 10 sample companies and researchers used time series or panel data regression analysis using the selected model, namely the REM model which is more reliable and suitable than using the FEM and CEM models. The process of testing the hypothesis uses a linear regression model which uses eviews 9. The results of the study indicate that taxes have a fairly positive and significant effect on transfer pricing 0.0060 < 0.05 and tunneling incentives have a positive but not significant effect. 0.0905 > 0.05 on transfer pricing. The amount (R2) of taxes and tunneling incentives is 48.52% while the remaining 51.48% is influenced by other variables. 05 on transfer pricing. The amount (R2) of taxes and tunneling incentives is 48.52% while the remaining 51.48% is influenced by other variables. 05 on transfer pricing. The amount (R2) of taxes and tunneling incentives is 48.52% while the remaining 51.48% is influenced by other variables.